Manifestations of alienation and fetishism in Cyberspace - Albdour, Salman; Rimawi, Subhi (Jordan Journal of Social Sciences, 2021)
This study aims at tackling the linguistic and philosophical meanings of alienation and fetishism, both in view of an ontological event or a human psychological and social phenomenon, by analyzing their manifestations in cyberspace, which created a parallel world to our living world, created another parallel life to our real life, as well as fabricating a new pattern of existence. Following a critical approach, this study explores technical and other non-technical aspects that have a direct or indirect role in maximizing fetishism and alienation in that cyberspace that has governed mankind, and changed his life and his relationships with himself and with others and with nature, as well as the reason for the shift in his values and aesthetic judgments.